KELAYAKAN POTENSI DAERAH DALAM MENDUKUNG PENGEMBANGAN INVESTASI DI JAWA TENGAH - Soebandriyo Soebandriyo; Slamet Santoso; Hendro Saptono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Research target : Analysing factors of determinant of dimension elegibility punish, phenomenon of handling of invesment management seen from aspect yuridis, giving recommend to Local Government Prov. Jateng in development of invesment potency, descriptive approach qualitative, with conclusion : 1.Kelayakan district potency from aspect of regulasi invesment : Komitmen Elite, private sector support, socialize, regulasi, prasarana and medium, readiness of institute, licensing amenity, ketersediaan of industrial area farm, labour with fee reached. Less be inwrought in promotion and cooperation, Some arrangement of invesment area still be unfavourable, support of regulasi Invesment have Whether applying punish contract not yet optimal, handling of collision and Related/Relevant gift sanksi good enough invesment, 2.Kelayakan regulasi of supporter of investasi:Regulasi ketenagakerjaan expressed [by] have supported, Regulasi Kewenangan expressed not yet supported, 3.Kajian invesment contract : Understanding of characteristic contract invesment still wear away, Legal fundament contract, related/relevant especially with procedure or execution step contract not yet there [is], Preparation contract invesment better be [done/conducted] to use or as according to step contract invesment